2017
DOI: 10.1002/tox.22409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methomyl on sex steroid hormone and vitellogenin levels in serum of male tilapia (Oreochromis niloticus ) and recovery pattern

Abstract: Tilapia were exposed to sub-lethal concentrations of 0, 0.2, 2, 20 or 200 μg/L for 30 days, then transferred to methomyl-free water for 18 days. E , T, 11-KTand VTG in serum were examined. There were no significant changes in all the parameters in serum of tilapia exposed to 0.2 μg/L and 2 μg/L methomyl compared to the control. However, 20 μg/L and 200 μg/L have the potential to disrupt the endocrine system of male tilapia, as shown by its ability to increase VTG and E and decrease T and 11-KT in serum. Thus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Because of its high solubility in water (57.9 g L −1 at 25 • C) and only weak to moderate adsorption in soils, methomyl has been detected in surface waters and food crops [1], with residues as high as 55.3 µg L −1 reported in environmental water [2]. Owing to its frequent detection in natural water bodies and its endocrine disruption potential in animals [3], the toxicity of methomyl to aquatic animals has attracted considerable attention [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Because of its high solubility in water (57.9 g L −1 at 25 • C) and only weak to moderate adsorption in soils, methomyl has been detected in surface waters and food crops [1], with residues as high as 55.3 µg L −1 reported in environmental water [2]. Owing to its frequent detection in natural water bodies and its endocrine disruption potential in animals [3], the toxicity of methomyl to aquatic animals has attracted considerable attention [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Sohoni et al [ 68 ] reported inhibition of both gonadal and somatic growth (weight and length) in males fathead minnows exposed to BPA concentrations of 640 and 1280 μg/L. GSI was significantly lower in mature carp naturally exposed to BPA from a highly polluted site and in O. niloticus exposed to 200 µg/L methomyl [ 62 , 69 ]. In the present study, the K-factor showed no conspicuous trend over months; however, it was declined in August and still at the same level in October.…”
Section: Discussionmentioning
confidence: 99%
“…The toxicological impacts of methomyl on aquatic animals, amphibians, land mammals, and humans are presented in Table 1. Reduction in the efficiency of the food chain in a Cr/Dg system [34] Different aspects of methomyl toxicity on tilapia as a model aquatic organism have been studied [15,35,36]. A high concentration of methomyl was found to drastically change biochemical and histological activities in tilapia.…”
Section: Toxicological Effects Of Methomyl Insecticidesmentioning
confidence: 99%
“…Environmental residues of methomyl can affect non-target organisms through the air, water, soil, and food chain ( Figure 2). Long-term exposure to methomyl can result in hepatotoxicity, cytotoxicity, and neurotoxicity in animals [15][16][17]. According to a survey conducted in France, 4.2% of the population was directly or indirectly poisoned with methomyl during the period 2012-2016 [18].…”
Section: Introductionmentioning
confidence: 99%